Alright, 1, 2, and 4 are correct but 3 is not.
The error you made could be hard to notice but it was made. So let's put the equation up, 6x-(2x-9)=-31. Your error occurred when you didn;t distribute the negative sign for (2x-9), if you woud have distributed it then the equation would then be simplified into 6x-2x+9=31. You then add like terms and get 4x+9=31, subtract 9 on both sides and you'll get 4x=22. Divide 4 on both sides to isolate the variable and you get x=5.5
Answer:
a square
Step-by-step explanation:
Answer:
- 8pq-3pq= 5pq
- 2m-3m+4 =4-m
Step-by-step explanation:
- The first equation shows two terms can be combine as follow: 8pq-3pq= (8-3)pq by applying common factoring. Then, because 8-3=5, it can be expressed as 5pq.
- In the second equation, we have only two terms that can be factored by combining the terms that share the same factor (which is m). Then, 2m-3m+4 can be expressed like m(2-3)+4. Because (2-3)=-1 and because the order of the sum does not affect the result, the result is 4-m.